Discovery and Functional Annotation of Quantitative Trait Loci Affecting Resistance to Sea Lice in Atlantic Salmon - Robledo, Diego; Gutiérrez, Alejandro P.; Barría, Agustín; Lhorente, Jean P.; Houston, Ross D.; Yáñez, José M. (Frontiers in Genetics, 2019)
Sea lice (Caligus rogercresseyi) are ectoparasitic copepods which have a large negative economic and welfare impact in Atlantic salmon (Salmo salar) aquaculture, particularly in Chile. A multi-faceted prevention and control strategy is required to tackle lice, and selective breeding contributes via cumulative improvement of host resistance to the parasite. While host resistance has been shown to be heritable, little is yet known about the individual loci that contribute to this resistance, the potential underlying genes, and their mechanisms of action. In this study we took a multifaceted approach to identify and characterise quantitative trait loci (QTL) affecting hoste resistance in a population of 2,688 Caligus-challenged Atlantic salmon post-smolts from a commercial breeding programme. We used low and medium density genotyping with imputation to collect genome-wide SNP marker data for all animals. Moderate heritablility estimates of 0.28 and 0.24 were obtained for lice density (as a measure of host resistance) and growth during infestation respectively. Three QTL explaining between 7 and 13 % of the genetic variation in resistance to sea lice (as represented by the traits of lice density) were detected on chromosomes 3, 18 and 21. Characterisation of these QTL regions was undertaken using RNA sequencing and pooled whole genome sequencing data. This resulted in the identification of a shortlist of potential underlying causative genes, and candidate functional mutations for further study. For example, candidates within the chromosome 3 QTL include a putative premature stop mutation in TOB1 (an anti-proliferative transcription factor involved in T cell regulation) and an uncharacterized protein which showed significant differential allelic expression (implying the existence of a cis-acting regulatory mutation). While host resistance to sea lice is polygenic in nature, the results of this study highlight significant QTL regions together explaining a moderate proportionbetween 7 and 13 % of the heritability of the trait. Future investigation of these QTL may enable improved knowledge of the functional mechanisms of host resistance to sea lice, and incorporation of functional variants to improve genomic selection accuracy.